2002
DOI: 10.1890/0012-9658(2002)083[1586:pdistu]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Population Differences in Sensitivity to Uv-B Radiation for Larval Long-Toed Salamanders

Abstract: Ultraviolet‐B radiation (UV‐B; 280–320 nm) penetrates some aquatic habitats to biologically significant depths and can alter life histories of aquatic organisms, including algae, zooplankton, fish, and amphibians. Although major species differences have been documented for UV‐B sensitivity, few studies have examined differences between populations of the same species. Previous work has suggested the hypothesis that larval long‐toed salamanders (Ambystoma macrodactylum) from valley populations (∼100 m elevation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Briefly, field and laboratory studies have shown that exposure to UVR can reduce survival, reduce growth, slow the rate of development, induce developmental malformations and abnormalities, reduce locomotor performance, and cause changes in metabolic rate and behaviour (Table 1). Such lethal and sublethal UVR effects have been observed in the embryos, larvae, metamorphs and adults of Limnodynastes peronii Artificial lamps [147] Lithobates sylvaticus Artificial lamps [93] Litoria aurea Ambient sunlight [177] Pseudacris cadaverina Ambient sunlight [179] Rana aurora Ambient sunlight plus artificial lamps [96] Rana cascadae Ambient sunlight [100] Taricha torosa Ambient sunlight [179] Reduced larval survival Ambystoma laterale Ambient sunlight plus artificial lamps [181] Ambystoma macrodactylum Artificial lamps [78,182] Ambystoma maculatum Ambient sunlight plus artificial lamps [181] Anaxyrus americanus Ambient sunlight plus artificial lamps [181] Artificial lamps [93] Bufo bufo Ambient sunlight [180,183] Crinia signifera Ambient sunlight [114] Hyla versicolor Ambient sunlight plus artificial lamps [181] Artificial lamps [93] Hypsiboas pulchellus Artificial lamps [69] Ichthyosaura alpestris Ambient sunlight [81] Artificial lamps [81] Limnodynastes peronii Artificial lamps [62,65] Lithobates clamitans Ambient sunlight [184] Ambient sunlight plus artificial lamps [181] Artificial lamps [93] Lithobates pipiens Ambient sunlight [184][185][186] Artificial lamps [58] Lithobates septentrionalis Ambient sunlight [184] Lithobates sylvaticus Ambient sunlight [188] Ambient sunlight plus artificial lamps …”
Section: Effects Of Uvr On Amphibiansmentioning
confidence: 99%
“…Briefly, field and laboratory studies have shown that exposure to UVR can reduce survival, reduce growth, slow the rate of development, induce developmental malformations and abnormalities, reduce locomotor performance, and cause changes in metabolic rate and behaviour (Table 1). Such lethal and sublethal UVR effects have been observed in the embryos, larvae, metamorphs and adults of Limnodynastes peronii Artificial lamps [147] Lithobates sylvaticus Artificial lamps [93] Litoria aurea Ambient sunlight [177] Pseudacris cadaverina Ambient sunlight [179] Rana aurora Ambient sunlight plus artificial lamps [96] Rana cascadae Ambient sunlight [100] Taricha torosa Ambient sunlight [179] Reduced larval survival Ambystoma laterale Ambient sunlight plus artificial lamps [181] Ambystoma macrodactylum Artificial lamps [78,182] Ambystoma maculatum Ambient sunlight plus artificial lamps [181] Anaxyrus americanus Ambient sunlight plus artificial lamps [181] Artificial lamps [93] Bufo bufo Ambient sunlight [180,183] Crinia signifera Ambient sunlight [114] Hyla versicolor Ambient sunlight plus artificial lamps [181] Artificial lamps [93] Hypsiboas pulchellus Artificial lamps [69] Ichthyosaura alpestris Ambient sunlight [81] Artificial lamps [81] Limnodynastes peronii Artificial lamps [62,65] Lithobates clamitans Ambient sunlight [184] Ambient sunlight plus artificial lamps [181] Artificial lamps [93] Lithobates pipiens Ambient sunlight [184][185][186] Artificial lamps [58] Lithobates septentrionalis Ambient sunlight [184] Lithobates sylvaticus Ambient sunlight [188] Ambient sunlight plus artificial lamps …”
Section: Effects Of Uvr On Amphibiansmentioning
confidence: 99%
“…Blaustein, 1994). In fact, population-specific vulnerability has recently been documented in both terrestrial (Belden & Blaustein 2002) and subtidal marine organisms (Gleason & Wellington 1995) where populations in habitats with high levels of UVR showed decreased vulnerability than populations occurring in environments with low UVR. Our aim was to similarly examine the response of organisms that lay in differentially UVRexposed habitats in the marine intertidal environment.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand differences in response across a range of UV‐B and predator experience, we tested individuals of two amphibian species from both high and low elevation populations. In general, UV‐B intensities become stronger with increasing elevation, exposing high elevation amphibian populations to significantly stronger UV‐B pressure relative to lower populations (Cockell & Blaustein, 2001; Belden & Blaustein, 2002b). We predicted a stronger UV‐B defense response in individuals from high elevation populations (Fig.…”
Section: Introductionmentioning
confidence: 99%